High-throughput characterization of Echinococcus spp. metacestode miRNomes - Cucher, Marcela Alejandra (2015)
Echinococcosis is a worldwide zoonosis of great public health concern, considered a neglected disease by the World Health Organisation. The cestode parasites Echinococcus granulosus sensu lato (s. l.) and Echinococcus multilocularis are the main aetiological agents. In the intermediate host, these parasites display particular developmental traits that lead to different patterns of disease progression. In an attempt to understand the causes of these differences, we focused on the analysis of microRNAs (miRNAs), small non-coding regulatory RNAs with major roles in development of animals and plants. In this work, we analysed the small RNA expression pattern of the metacestode, the stage of sanitary relevance, and provide a detailed description of Echinococcus miRNAs. Using high-throughput small RNA sequencing, we believe that we have carried out the first experimental identification of miRNAs in E. multilocularis and have expanded the Echinococcus miRNA catalogue to 38 miRNA genes, including one miRNA only present in E. granulosus s. l. Our findings show that although both species share the top five highest expressed miRNAs, 13 are differentially expressed, which could be related to developmental differences. We also provide evidence that uridylation is the main miRNA processing mechanism in Echinococcus spp. These results provide detailed information on Echinococcus miRNAs, which is the first step in understanding their role in parasite biology and disease establishment and/or progression, and their future potential use as drug or diagnostic targets.